Antioxidant and Photoprotective Activity of Bromelain Cream: An In Vitro and In Vivo Study - Zahra Marissa; Soraya Ratnawulan Mita; Cahya Khairani Kusumawulan; Sriwidodo Sriwidodo (Cosmetics)
Bromelain, a natural enzyme derived from pineapple, is known for its antioxidant properties, and its potential as a photoprotective agent has garnered interest in skincare applications. The primary objective of this research was to evaluate and optimize the effectiveness of bromelain-based creams in providing antioxidant and photoprotective protection against ultraviolet (UV) radiation. Antioxidant activity was assessed using the DPPH radical scavenging assay, and the Sun Protection Factor (SPF) was determined in vitro and in vivo to evaluate photoprotective activity. The results revealed that bromelain exhibited strong antioxidant activity. Photoprotection, as measured by SPF, the formulation F3, which combined bromelain with other UV filters, exhibited the highest SPF values of 22.043 ± 0.277 (in vitro) and 21.3 ± 2.901 (in vivo), indicating enhanced photoprotective efficacy. This improvement in SPF was likely due to the synergistic effect of bromelain with the UV filters Octyl Methoxycinnamate (OMC). The findings suggest a positive correlation between antioxidant activity and photoprotection, with bromelain’s antioxidant properties contributing to its overall photoprotective effect. Bromelain may be used on people without causing skin or eye irritation. This study supports the potential of bromelain-based creams as dual-action skincare formulations, offering both antioxidant and UV protection.